Causes and effects between attitudes, the built environment and car kilometres: A longitudinal analysis - van de Coevering, Paul; Maat, Kees; van Wee, Bert (Journal of transport geography, 2021)
Travel-related attitudes are believed to affect the connections between the built environment and travel behaviour. Previous studies found supporting evidence for the residential self-selection hypothesis which suggests that the impact of the built environment on travel behaviour could be overestimated when attitudes are not accounted for. However, this hypothesis is under scrutiny as the reverse causality hypothesis, which implies a reverse direction of influence from the built environment towards attitudes, is receiving increased attention in recent research. This study tests both directions of influence by means of cross-sectional and longitudinal structural equation models. GPS tracking is used to assess changes in travel behaviour in terms of car kilometres travelled. The outcomes show stronger reverse causality effects than residential self-selection effects and that land-use policies significantly reduce car kilometres travelled. Moreover, the longitudinal models show that the built environment characteristics provide a better explanation for changes in car kilometres travelled than the travel-related attitudes. This contradicts the cross-sectional analysis where associations between car kilometres travelled and travel-related attitudes were stronger. This highlights the need for more longitudinal studies in this field. •Cross-sectional and longitudinal structural equation models are estimated to test rival hypotheses of residential self-selection and reverse causality.•Reverse causality effects tend to be stronger than residential self-selection effects.•Residential self-selection effects are not only based on attitudes, but also on previous number of car kilometres travelled.•In addition to RSS, the built environment significantly influences car kilometres travelled.•The impact of the built environment on changes in travel behaviour is strong compared to other determinants.